MXene-based 2D nanomaterials for solar cells - Aziz, M. F.; Azam, Mohd Asyadi (CRC Press, 2022)
The titanium-carbide MXenes, Ti3C2Tx, where T signifies some surface-terminating functional groups (oxygen-hydrogen bond, oxygen bond and fluorine bond) or well known as MXenebased 2D nanomaterials has various advantages such as good electrical conductivity, provide high transport charge carrier, superb visibility, highly work function tunability and excellent mechanical toughness. This unique physical of MXene two-dimensional nanomaterials demonstrates that highly potential use for different type of solar cells such as perovskite, silicon, organic, quantum dot-sensitized and dye sensitized. In this chapter, the utilizing of MXene two-dimensional nanomaterials as electrode materials, additive, and hole transport layer/electron transport layer (HTL/ETL) in various solar cells application will be discussed and explained. Numerous analysis such as scanning electron microscope (SEM), x-ray diffraction (XRD), cyclic voltammetry (CV), and electrochemical impedance spectroscopy (EIS) will be described here. Generally, the basic studies of solar cells parameter are including open-circuit voltage (Voc), fill factor (ff), short-circuit current density (Jsc) and the solar cell efficiency (η). Thus, the performance of solar cells employing of MXene two dimensional nanomaterials also will be presented and analysed in this chapter. It is understood that from this MXene two-dimensional nanomaterials overview will assists a complete and knowledge into the current research work and provide a new progress for the research of this MXenes in the solar cells.